A gallium adsorbent, method of preparation and use

CN118847025BActive Publication Date: 2026-10-09WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411058205.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2026-10-09
Estimated Expiration
2044-08-02

AI Technical Summary

Technical Problem

[0005]针对现有吸附剂对低浓度稀散金属镓吸附效率低、选择性吸附和重复利用性能差的问题,本发明的目的在于提供一种镓吸附剂、制备方法和应用

Benefits of technology

本发明利用含氮有机物对氧化钼进行氮掺杂,得到的氮掺杂氧化钼基纳米线具有暴露的羟基、羧基等活性位点,不但对镓离子具有吸附作用,而且掺杂的氮原子与镓离子形成配位作用,进一步提高了吸附效率,与未掺杂含氮有机物的氧化钼相比,吸附效率提高了1.12倍。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118847025B_ABST
    Figure CN118847025B_ABST
Patent Text Reader

Abstract

The application discloses a gallium adsorbent, a preparation method and application, and the gallium adsorbent is nitrogen-doped molybdenum oxide-based nanowires formed by pyrolysis of molybdate and nitrogen-containing organic matter. The application utilizes nitrogen-containing organic matter to perform nitrogen doping on molybdenum oxide, and the obtained nitrogen-doped molybdenum oxide-based nanowires realize high-efficiency selective adsorption of gallium ions in an impurity ion coexisting system, and the adsorption of gallium ions has excellent cycle stability, and the problems of low adsorption efficiency, poor selective adsorption and poor recycling performance of a low-concentration scattered metal gallium in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of rare and dispersed metal gallium recovery technology, specifically relating to a gallium adsorbent, its preparation method, and its application. Background Technology

[0002] Gallium, as an important mineral resource, has been widely used in various green technology fields such as semiconductors, photovoltaic solar cells, optical fiber communication, infrared optics, medical devices, and magnetic materials. Due to gallium's irreplaceable nature, the demand for gallium will increase significantly in the future, with global gallium resource demand predicted to reach 720 tons by 2025. However, gallium's "scarcity," "occurrence," and "fine-grained" characteristics make it extremely difficult to form minerals, and it often exists in the form of occurrence minerals.

[0003] Currently, gallium is typically recovered from materials such as bauxite, red mud, Bayer solution, zinc ore, coal, fly ash, and waste electronic products. Gallium ion recovery methods include chemical precipitation, electrochemical methods, solvent extraction, and adsorption. Chemical precipitation is hampered by drawbacks such as secondary pollution, poor selectivity, and low gallium extraction purity. Electrochemical methods are mainly used for the purification stage of gallium ions, but suffer from high energy consumption and low current efficiency. Extractants such as P507, TBP, and Cyanex 272 still play an important role in industrial gallium recovery, but they have disadvantages such as expensive raw materials, complex processes, potential generation of toxic substances, low extractant reuse rate, and poor back-extraction efficiency.

[0004] Compared to the methods mentioned above, adsorption is considered an economical and effective method for gallium ion recovery due to its simple operation and low secondary pollution. Currently, adsorbents used for gallium recovery mainly include modified and activated carbon-based materials (such as carbon nanotubes and graphene oxide) and silicon-based materials, ion exchange resins containing amine oxime groups, and polyurethane foams. However, these materials exhibit low adsorption efficiency for low concentrations of rare and dispersed gallium, poor selective adsorption, and poor reusability. Therefore, developing an economical and effective adsorbent for the recovery of low-concentration gallium ions is of great significance. Summary of the Invention

[0005] To address the problems of low adsorption efficiency, poor selective adsorption, and poor reusability of existing adsorbents for low concentrations of rare and dispersed gallium, the present invention aims to provide a gallium adsorbent, its preparation method, and its application.

[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a gallium adsorbent, which is a nitrogen-doped molybdenum oxide-based nanowire formed by the pyrolysis of molybdate and nitrogen-containing organic matter.

[0007] Secondly, the present invention provides a method for preparing a gallium adsorbent, comprising the following steps: S1: Dissolve molybdate and nitrogen-containing organic matter in a solvent to obtain a mixed solution; S2: Adjust the pH of the mixed solution to 4-6 using an inorganic acid until a white precipitate appears to obtain the reaction solution; then heat the reaction solution, and after solid-liquid separation, washing, and drying, obtain the precursor; S3: The precursor is pyrolyzed in an inert gas atmosphere to obtain a gallium adsorbent.

[0008] Preferably, the molybdate is one or more of ammonium molybdate, potassium molybdate, and sodium molybdate; the nitrogen-containing organic compound is one or more of aniline, ethylenediamine, and pyridine.

[0009] Preferably, the molar ratio of nitrogen-containing organic matter to molybdenum atoms in molybdate is (0.35-3):1.

[0010] Preferably, the inorganic acid is 1-3 M hydrochloric acid.

[0011] Preferably, in step S2, the heating temperature is 40-100℃ and the heating time is 3-10 h.

[0012] Preferably, in step S3, the pyrolysis temperature is 300-400℃ and the pyrolysis time is 4-6h.

[0013] Thirdly, the present invention provides a method for enriching gallium ions from a gallium-containing leachate, comprising the following steps: adjusting the pH of the gallium-containing leachate to 2.0-4.0, adding the gallium adsorbent as described in the first aspect to the gallium-containing leachate, mechanically stirring for 50-70 minutes, and after solid-liquid separation, obtaining the gallium-enriched adsorbent and the adsorbed liquid.

[0014] Preferably, the concentration of gallium ions in the gallium-containing leachate is 10-100 mg / L. -1 For example, it could be a leachate obtained from leaching bauxite, zinc ore, or coal, with an average gallium ion concentration of 10-50 ppm.

[0015] Preferably, the liquid-solid ratio of gallium-containing leachate to gallium adsorbent is 100 mL: 10-30 mg.

[0016] The beneficial effects of this invention are: This invention utilizes nitrogen-containing organic matter to dope molybdenum oxide with nitrogen. The resulting nitrogen-doped molybdenum oxide-based nanowires have exposed active sites such as hydroxyl and carboxyl groups. They not only adsorb gallium ions, but the doped nitrogen atoms also form coordination with gallium ions, further improving the adsorption efficiency. Compared with undoped molybdenum oxide containing nitrogen-containing organic matter, the adsorption efficiency is increased by 1.12 times.

[0017] The gallium adsorbent provided by this invention has a positive effect on Cu. 2+ Al 3+ Ni2+ Zn 2+ The selective separation coefficients are 58.4, 90.9, 102.3 and 299.1, respectively, which enables selective adsorption of gallium ions and avoids interference from other coexisting ions.

[0018] The gallium adsorbent provided by this invention exhibits an adsorption efficiency of up to 94.5% for gallium ions after five adsorption-desorption cycles, demonstrating excellent cycle stability. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings of the embodiments will be briefly described below.

[0020] Figure 1 SEM images of nitrogen-doped molybdenum oxide nanowires and pure molybdenum oxide prepared in Example 1; Figure 2 XRD patterns of the precursor and nitrogen-doped molybdenum oxide nanowires prepared in Example 1; Figure 3 The adsorption performance of gallium ions on nitrogen-doped molybdenum oxide nanowires prepared in Example 1 at different times; Figure 4 The images show the FTIR spectra of the nitrogen-doped molybdenum oxide nanowires prepared in Example 1 before and after gallium ion adsorption. Figure 5 The adsorption performance of nitrogen-doped molybdenum oxide nanowires and pure molybdenum oxide for gallium ions at different times is shown in Example 1. Figure 6 The adsorption performance of gallium ions on the nitrogen-doped molybdenum oxide-based nanowires prepared in Example 1 over 5 consecutive cycles; Figure 7 The adsorption performance of gallium ions on nitrogen-doped molybdenum oxide nanowires prepared in Example 1 under different pH conditions; Figure 8 The adsorption performance of nitrogen-doped molybdenum oxide nanowires prepared in Example 1 for gallium ions of different concentrations; Figure 9 The effect of coexisting ions on the adsorption of gallium ions by nitrogen-doped molybdenum oxide nanowires prepared in Example 1. Detailed Implementation

[0021] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0022] Example 1 A gallium adsorbent, the preparation method of which includes the following steps: S1: Ammonium molybdate ((NH4)6Mo7O) 24 •4H2O) and ethylenediamine were dissolved in 90 mL of water to obtain a mixed solution; S2: Slowly add 2M hydrochloric acid dropwise to the mixed solution to adjust the pH to 5 until a white precipitate is observed, thus obtaining the reaction solution. Heat the reaction solution at 50℃ for 5 hours, filter the product, wash it with ethanol, and then dry it in an oven at 60℃ for 12 hours to obtain the precursor; S3: The precursor is placed in a crucible and pyrolyzed in a tube furnace under a nitrogen atmosphere at a temperature of 300°C. After 5 hours, the tube furnace is closed, the sample is cooled and removed, and nitrogen-doped molybdenum oxide nanowires, i.e. gallium adsorbent, are obtained.

[0023] Figure 1 These are SEM images of nitrogen-doped molybdenum oxide nanowires and pure molybdenum oxide prepared in this embodiment. Figure 1 (a) is a nitrogen-doped molybdenum oxide-based nanowire. Figure 1 (b) is pure molybdenum oxide without ethylenediamine doping. It can be seen that the adsorbent prepared in this invention has a nanowire morphology.

[0024] Figure 2 The images shown are XRD patterns of the precursor and nitrogen-doped molybdenum oxide-based nanowires in this embodiment. Figure 2 (a) is a precursor. Figure 2 (b) shows nitrogen-doped molybdenum oxide nanowires and pure molybdenum oxide. It can be seen that the nanowires prepared by this invention have an amorphous structure.

[0025] Example 2 A method for enriching gallium ions includes the following steps: Take a concentration of 50 mg / L -1 100 mL of gallium nitrate solution was prepared, and the pH of the solution was adjusted to 4.0 with sodium hydroxide / dilute nitric acid. Then, 30 mg of the gallium adsorbent prepared in Example 1 was added, and the mixture was stirred at 250 rpm on a magnetic stirrer. Samples were taken at different time intervals and filtered through a 0.22 μm aqueous filter. The concentration of gallium ions in the solution before and after adsorption was measured using an atomic absorption spectrometer (Shimadzu AA-6680). The results are as follows: Figure 3 As shown, the nitrogen-doped molybdenum oxide-based nanowires prepared in this invention exhibit good performance at pH 4.0 for 50 mg L⁻¹ -1 The adsorption efficiency of gallium ions is as high as 99.8%, and the maximum adsorption capacity is 156.9 mg g. -1 After 60 minutes of adsorption, equilibrium is reached. Figure 4The images show the FTIR spectra of nitrogen-doped molybdenum oxide nanowires before and after gallium ion adsorption. It can be seen that the 3425 cm⁻¹ height is due to the stretching vibration of the -OH group. -1 The absorption peak at 3397 cm⁻¹ showed a broad intensity decay after gallium ion adsorption and shifted to a lower wavenumber region. -1 This indicates that -OH groups participated in the adsorption reaction of gallium ions. The ions were bound at 486 cm⁻¹. -1 and 1066 cm -1 The tensile vibration peaks of Ga-O and Ga-OH generated at the site indicate that MoO x The gallium ion adsorption mechanism of / N involves the interaction of gallium ions with H in the -OH group. + Exchange. Due to a significant reduction in the corresponding C≡N tensile vibration peak, and at 570 cm⁻¹... -1 The weak peak observed was due to Ga-N stretching vibration, further confirming the nitrogen-doped enhanced adsorption performance.

[0026] Figure 5 Nitrogen-doped molybdenum oxide nanowires (MoO) x / N) and molybdenum oxide (MoO) x The adsorption performance of gallium ions at different times shows that amorphous molybdenum oxide doped with nitrogen-containing organic matter is beneficial to the adsorption of gallium ions, and the adsorption efficiency is increased by 1.12 times compared with undoped molybdenum oxide.

[0027] Figure 6 The adsorption performance of nitrogen-doped molybdenum oxide nanowires for gallium ions in 5 consecutive cycles shows that the gallium adsorbent prepared in this invention has an adsorption efficiency of up to 94.5% after 5 adsorption-desorption cycles, exhibiting excellent cycle stability.

[0028] Example 3 A method for enriching gallium ions includes the following steps: Take 50 mg L of each -1 100 mL of gallium nitrate solution was placed in four beakers, and the pH of the solution was adjusted to 2.0, 2.5, 3.0, 3.5, and 4.0 respectively using sodium hydroxide / dilute nitric acid. Then, 30 mg of the gallium adsorbent prepared in Example 1 was added, and the mixture was stirred at 250 rpm on a magnetic stirrer. After 4 h, samples were taken and filtered through a 0.22 μm aqueous filter. The concentration of gallium ions in the solution before and after adsorption was measured using an atomic absorption spectrometer (Shimadzu AA-6680). The results are as follows: Figure 7 As shown, the nitrogen-doped molybdenum oxide-based nanowires prepared in this invention can achieve efficient adsorption of gallium ions in acidic solutions, and the adsorption effect is better at pH 3.0~4.0.

[0029] Example 4 A method for enriching gallium ions includes the following steps: Take 10 mg L of each -1 and 100 mg L -1 100 mL of gallium nitrate solution was placed in two beakers, and the pH of the solution was adjusted to 4.0 with sodium hydroxide / dilute nitric acid. Then, 30 mg of the gallium adsorbent prepared in Example 1 was added, and the mixture was stirred at 250 rpm on a magnetic stirrer. Samples were taken at different time intervals and filtered through a 0.22 μm aqueous filter. The concentration of gallium ions in the solution before and after adsorption was measured using an atomic absorption spectrometer (Shimadzu AA-6680). The results are as follows: Figure 8 As shown in the figure, the gallium adsorbent prepared in this invention can adsorb gallium at concentrations of 10-100 mg / L. -1 The gallium ion adsorbent provided in this invention achieves efficient adsorption at low concentrations. The Langmuir isotherm model predicts a maximum adsorption capacity (qe) of up to 380.9 mgg. -1 The adsorption capacity was increased by 1.9-112.0 times compared to previously reported gallium adsorbents (carbon-based materials, silicon-based materials, cellulose, ion-imprinted materials, polymer resins, etc.).

[0030] Example 5 A method for enriching gallium ions includes the following steps: A metal ion concentration of 50 mg / L was prepared using gallium nitrate, copper nitrate, zinc nitrate, aluminum nitrate, and nickel nitrate. -1 A mixed solution was prepared. 100 mL of the above mixed solution was taken, and the pH was adjusted to 4.0 with sodium hydroxide / dilute nitric acid. Then, 30 mg of the gallium adsorbent prepared in Example 1 was added, and the solution was stirred at 250 rpm on a magnetic stirrer. After 4 h, a sample was taken and filtered through a 0.22 μm aqueous filter. The concentration of gallium ions in the solution before and after adsorption was measured using an atomic absorption spectrometer (Shimadzu AA-6680), and the recovery efficiency was calculated. Figure 9 As shown, it can be seen that Al, which has the same ionic radius and valence state as gallium ions, can be used to... 3+ Cu commonly found in acid leaching systems 2+ Zn 2+ Ni 2+ As coexisting ions. The nitrogen-doped molybdenum oxide-based nanowires prepared in this invention are paired with Cu... 2+ Al 3+ Ni 2+ Zn 2+ The selective separation coefficients were 58.4, 90.9, 102.3, and 299.1, respectively, indicating selective adsorption of gallium ions.

[0031] In summary, the nitrogen-doped molybdenum oxide-based nanowires prepared by the present invention via a low-temperature pyrolysis method utilize Cu impurity ions. 2+ Zn 2+ Al 3+ Ni 2+ The coexistence system achieves highly efficient and selective adsorption of gallium ions in acidic solutions, and exhibits excellent cycle stability for the adsorption of gallium ions, solving the problems of low adsorption efficiency, poor selective adsorption and reusability of low-concentration rare gallium metals in existing technologies.

[0032] It should be noted that all the above embodiments belong to the same inventive concept, and the descriptions of each embodiment have different focuses. Where the description in a particular embodiment is not detailed, please refer to the description in other embodiments.

[0033] The embodiments described above are merely illustrative of implementation methods of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A method for enriching gallium ions from a gallium-containing leachate, characterized in that, Includes the following steps: The pH of the gallium-containing leaching solution was adjusted to 3.0-4.

0. The gallium adsorbent was added to the gallium-containing leaching solution and mechanically stirred for 50-70 minutes. After solid-liquid separation, gallium-enriched adsorbent and adsorbed liquid were obtained. The gallium adsorbent is formed by the pyrolysis of molybdate and nitrogen-containing organic matter into nitrogen-doped molybdenum oxide-based nanowires.

2. The method for enriching gallium ions in a gallium-containing leachate according to claim 1, characterized in that, The method for preparing the gallium adsorbent includes the following steps: S1: Dissolve molybdate and nitrogen-containing organic matter in a solvent to obtain a mixed solution; S2: Adjust the pH of the mixed solution to 4-6 using an inorganic acid until a white precipitate appears to obtain a reaction solution; then heat the reaction solution, and after solid-liquid separation, washing, and drying, obtain the precursor; S3: The precursor is pyrolyzed in an inert gas atmosphere to obtain the gallium adsorbent.

3. The method for enriching gallium ions in a gallium-containing leaching solution according to claim 2, characterized in that, The molybdate is one or more of ammonium molybdate, potassium molybdate, and sodium molybdate; the nitrogen-containing organic compound is one or more of aniline, ethylenediamine, and pyridine.

4. The method for enriching gallium ions in a gallium-containing leachate according to claim 2, characterized in that, The molar ratio of the nitrogen-containing organic compound to the molybdate atoms in the molybdate is (0.35-3):

1.

5. The method for enriching gallium ions in a gallium-containing leachate according to claim 2, characterized in that, The inorganic acid is 1-3 M hydrochloric acid.

6. The method for enriching gallium ions in a gallium-containing leaching solution according to claim 2, characterized in that, In step S2, the heating temperature is 40-100℃ and the heating time is 3-10 h.

7. The method for enriching gallium ions in a gallium-containing leaching solution according to claim 2, characterized in that, In step S3, the pyrolysis temperature is 300-400℃ and the pyrolysis time is 4-6h.

8. The method for enriching gallium ions from a gallium-containing leachate according to claim 1, characterized in that, The concentration of gallium ions in the gallium-containing leachate is 10-100 mg / L. -1 .

9. The method for enriching gallium ions from a gallium-containing leachate according to claim 1, characterized in that, The liquid-solid ratio of the gallium-containing leachate to the gallium adsorbent is 100 mL: 10-30 mg.